2015
DOI: 10.3389/fgene.2015.00006
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of kidney disease and related cardiometabolic phenotypes in Zuni Indians: the Zuni Kidney Project

Abstract: The objective of this study is to identify genetic factors associated with chronic kidney disease (CKD) and related cardiometabolic phenotypes among participants of the Genetics of Kidney Disease in Zuni Indians study. The study was conducted as a community-based participatory research project in the Zuni Indians, a small endogamous tribe in rural New Mexico. We recruited 998 members from 28 extended multigenerational families, ascertained through probands with CKD who had at least one sibling with CKD. We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 79 publications
(90 reference statements)
0
29
0
Order By: Relevance
“…In addition to sequence variations in OT pathway genes, epigenetic modifications of the OXTR gene have recently attracted considerable attention in clinical, behavioral, and cognitive neurosciences (Kumsta et al, 2013) and have been associated with different phenotypes including maternal PPD (Bell et al, 2015; Kimmel et al, 2016), amygdala reactivity (Puglia et al, 2015), autism (Gregory et al, 2009), and social anxiety disorder (Ziegler et al, 2015) amongst others. Briefly, epigenetics encompasses a set of biochemical modifications of genome function (e.g., histone modifications, DNA methylation, or the effects of small non-coding RNAs, e.g., micro RNAs) that interfere with transcriptional or translational events and can therefore regulate gene expression.…”
Section: Gene-environment Interactions and Epigenetic Modificationmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to sequence variations in OT pathway genes, epigenetic modifications of the OXTR gene have recently attracted considerable attention in clinical, behavioral, and cognitive neurosciences (Kumsta et al, 2013) and have been associated with different phenotypes including maternal PPD (Bell et al, 2015; Kimmel et al, 2016), amygdala reactivity (Puglia et al, 2015), autism (Gregory et al, 2009), and social anxiety disorder (Ziegler et al, 2015) amongst others. Briefly, epigenetics encompasses a set of biochemical modifications of genome function (e.g., histone modifications, DNA methylation, or the effects of small non-coding RNAs, e.g., micro RNAs) that interfere with transcriptional or translational events and can therefore regulate gene expression.…”
Section: Gene-environment Interactions and Epigenetic Modificationmentioning
confidence: 99%
“…Methylation-induced downregulation of the OTR was also confirmed in post mortem cortical brain tissue of male patients with autism spectrum disorders (Gregory et al, 2009). Two recent studies revealed a role for OXTR DNA methylation in peripheral blood cells to predict risk for PPD (Bell et al, 2015; Kimmel et al, 2016). GG homozygous (rs53576) women, who were not depressed during pregnancy had an almost 3-fold risk ( adjusted OR: 2.63 ) to develop PPD for every 10% increase of DNA methylation at a CpG dinucleotide located on intron 1, 934 basepairs upstream of the translation start site (CpG −934) compared to A allele carriers.…”
Section: Gene-environment Interactions and Epigenetic Modificationmentioning
confidence: 99%
See 3 more Smart Citations